Impact of nearby lightning on photovoltaic modules converters. Issue 2 (16th November 2021) - Barmada, Sami; Formisano, Alessandro; Hernandez, Jesus C.; Sánchez Sutil, Francisco José J.; Petrarca, Carlo
Abstract : Purpose: The lightning phenomenon is one of the main threats in photovoltaic (PV) applications. Suitable protection systems avoid major damages from direct strikes but also nearby strikes may induce overvoltage transients in the module itself and in the power conditioning circuitry, which can permanently damage the system. The effects on the PV system sensibly depend on the converter topology and on the adopted power switch. In the present study, a comparative analysis of the transient response due to a nearby lightning strike (LS) is carried out for three PV systems, each equipped with a different converter, namely, boost, buck and buck–boost, based on either silicon carbide metal oxide semiconductor field effect transistors (SiC MOSFET) or insulated gate bipolar transistors controlled power switch devices, allowing in this way an analysis at different switching frequencies. The purpose of this paper is to present the results of the numerical analysis to help the design of suited protection systems. Design/methodology/approach: Using a recently introduced three-dimensional semi-analytical method to simulate the electromagnetic transients caused in PV modules by nearby LSs, we investigate numerically the effect of a LS on the electronic circuits connecting the module to the alternate current (AC) power systems. This study adopts numerical simulations because experimental analyses are not easy to perform and does not grant a sufficient coverage of all statistically relevant aspects. The approach was validated in a previous paper against available experimental data. Findings: It is found that the load voltage is not severely interested by the strike effects, thanks to the low pass filters present at the converter output, whereas a relatively high overvoltage develops between the negative pin of the inner circuitry and the "ground" voltage reference. The overcurrent present in the active switches is hardly comparable because of the different topologies and working frequencies; however, the highest overcurrent is observed in the buck converter topology, with SiC MOSFET technology, although it shows the fastest decay. Originality/value: This research proposes, to the best of the authors' knowledge, a comprehensive comparison of the indirect lighting strike effects on the converter connected to PV panels. A proper design of the lightning and surge protection system should take into account such aspects to reduce the risk of induced overvoltage and overcurrent transients.